1998
DOI: 10.1086/513922
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Interleukin‐8 Concentration in Nasal Secretions and Severity of Symptoms of Experimental Rhinovirus Colds

Abstract: The purpose of this study was to examine the association between experimental rhinovirus infection and the elaboration of interleukin-8 (IL-8) into nasal secretions of volunteers and to determine the effect of pentoxifylline on IL-8 elaboration and rhinovirus-associated common cold symptoms. Fifty-four subjects with experimental rhinovirus infections and 20 sham-inoculated subjects were studied. Pentoxifylline had no effect on rhinovirus-induced symptoms or nasal-secretion IL-8 concentrations. IL-8 concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
2
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(124 citation statements)
references
References 23 publications
5
113
2
4
Order By: Relevance
“…Rhinovirus infection, as well as infection with other respiratory viruses, has been shown to stimulate production of IL-6, IL-8, and GM-CSF in nasal secretions of infected individuals and in cultures of primary respiratory epithelial cells or in human repiratory epithelial cell lines (7,8,10,11). IL-8 is thought to be primarily responsible for the neutrophil infiltration that is evident early after natural or experimental rhinovirus infection (7,11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rhinovirus infection, as well as infection with other respiratory viruses, has been shown to stimulate production of IL-6, IL-8, and GM-CSF in nasal secretions of infected individuals and in cultures of primary respiratory epithelial cells or in human repiratory epithelial cell lines (7,8,10,11). IL-8 is thought to be primarily responsible for the neutrophil infiltration that is evident early after natural or experimental rhinovirus infection (7,11).…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 is thought to be primarily responsible for the neutrophil infiltration that is evident early after natural or experimental rhinovirus infection (7,11). The objective of this study was to further characterize the chemokine response to rhinovirus infection using the BEAS-2B bronchial epithelial cell culture system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selective recruitment and activation of neutrophils seems linked to increased concentrations of IL-8, which has been shown to play a causative role in acute inflammation (Harada et al, 1994). Previous studies have also shown a correlation between IL-8 and severity of symptoms of cold, and this particular cytokine was constitutively present in studies of rhinovirus infection (Turner et al, 1998;Gern et al, 2002).…”
Section: List Of Abbreviationsmentioning
confidence: 96%
“…Rhinovirus infection of the nasal epithelium typically produces congestion and neutrophil infiltration and increased glandular secretions. The cytokines IL-1β, IL-6 and IL-8 have been found in the nasal secretions of symptomatic humans with experimental rhinovirus colds [103,128,154]. These very cytokines, in addition to TNF-α, are also induced by infection of cultured lung epithelial cells [64,123].…”
Section: Cytokines In Viral Respiratory Diseases Of Humansmentioning
confidence: 99%